Of Mice and Men movie poster. - Hal Roach Studios:::Creator::::::::::::
Of Mice and Men movie poster featuring Betty Field (Candy's Wife) Text reads "I'm decent I tell you...nobody's got no right to call me names" "The Picture Hollywood said could never be made" RESTRICTED USE Digital copy only. No hard copy.